Teaching mental health first aid in the school setting: a novel approach to improving outcomes for common adolescent mental disorders. Issue 4 (August 2018) - Hart, Laura M.; Cox, Georgina R.; Lees, Lucy
Abstract : Purpose of review: Common adolescent mental disorders, such as depression, often go untreated and severely impact health and educational outcomes. The purpose of this review is to describe what is currently known about school-based mental health interventions and to describe a new intervention, Mental Health First Aid training. Recent findings: Universal and selective prevention and treatment programmes have been widely evaluated, though population-level dissemination remains elusive. A novel approach is to train adolescents in how to recognise early signs of mental disorder onset, decrease stigmatising beliefs and barriers to help-seeking, and to use appropriate first aid strategies for assisting peers in mental health crisis, such as those with depression and suicidal ideation. Summary: Teaching adolescents the skills necessary to recognise and respond to mental health problems and mental health crises may provide life-long skills that prompt lower stigmatising beliefs, greater support of peers and appropriate, timely help-seeking.